Liver biopsy evaluation : - Kanel, Gary C. (W.B Saunders, 2000)
Introducing a highly illustrated microscope-side liver pathology reference. The text lists the presenting symptom and then follows through the process to arrive at a diagnosis. Divided into three sections, this reference provides an introduction to liver biopsy evaluation that includes basic morphologic information. This is a step-by-step guide to evaluation. The second section covers histological features seen under a microscope and lists potential diagnoses. The third section lists all liver diseases and includes the pathologic characteristics and clinical/laboratory features of each.